Pengaruh Kinerja Keuangan Terhadap Harga Saham PT. Krakatau Steel Tahun 2015-2019 - Trisbiani, Meyda Dewi; Rizqiyah, Amanatur; Novita, Amira Dian (IAIN Kudus, 2020)
PT. Krakatau Steel which is engaged in steel production has experienced a decline in financial performance. From this incident, the company has a large amount of debt and declining corporate profits. This study aims to determine the effect of Return on equity, and Debt to equity ratio on stock prices on the IDX. The population and sample in this study are the financial statement data of PT. Krakatau Steel 2015-2019. The data collected in this study uses how to download the company's Annual Report that we obtained from the official website of IDX. Analysis of the data used in this study uses the classic assumption test, multiple linear regression test, and hypothesis testing with the SPSS application program. The results of this study are the Return on equity variable, and the Debt to equity ratio has no significant effect on stock prices.